Estudio de Riesgos y Vulnerabilidades de la Red LAN y Equipos del Infocentro San Juan - Miranda Vera, Cristina Kriley (2019)
Actually, the technology is advancing and the government has been concerned with offering its access to technologies in rural areas, where technological services are offered to citizens through the infocenters. Because anyone can use of this service that is offered, these technologies are highly vulnerable and the data that is managed in these places is very important for users. In the present case study, an analysis of the risks and vulnerabilities in the LAN LAN and Infocentro equipment of “San Juan” was carried out, where it was used the MAGERIT methodology to analyze and manage risks directly related to the use of technologies. The PILAR software tool was implemented, which is designed to perform the risk analysis following the MAGERIT methodology. With this study of the risks and vulnerabilities of the LAN network of the Infocentro, the potential threats, vulnerabilities and risks for the information, infrastructure, equipment used in that place are identified. Small failures were found in the physical infrastructure of the network. Regarding the logical state of the data network, it was shown that there are no vulnerabilities that threaten security, because the infocenter uses Ubuntu as an operating system. It is recommended to promote the habit of the use of computer security by all users of the infocenter to create policies based on ethical values to form responsible users in the use of information technology